Airborne radar observations of rainband structure in Hurricane Ophelia (2005) - Razin, Naufal, author; Bell, Michael M., author (Colorado State University. Libraries, 2017)
One of the mechanisms proposed for the spin-up of the tropical cyclone (TC) mean tangential (swirling) circulation is the convergence of absolute angular momentum above the boundary layer in the outer-core region, which results in the broadening of the TC wind field. Mid-level inflow associated with TC rainband stratiform precipitation may be instrumental in spinning up the broader circulation and may be important in the development of secondary eyewalls. This analysis shows the concurrent presence of an elevated tangential wind maximum and a distinct mid-level inflow in the stratiform region, consistent with the proposed mechanism for TC intensity change.
240 - Naufal Bin Razin
Keywords: hurricane; rainbands; convective; stratiform